2014
DOI: 10.1039/c3tb21246g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bone regeneration with a gold nanoparticle–hydrogel complex

Abstract: A hybrid hydrogel composed of gelatin and gold nanoparticles (GNPs) was designed to evaluate the effect of new bone formation and proves itself to be useful as an implant material for treating defected bone tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
162
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(176 citation statements)
references
References 38 publications
(50 reference statements)
3
162
1
1
Order By: Relevance
“…68 Biodegradable gelatin hydrogel incorporating gold nanoparticles (average size 27±3 nm) was also studied. 70 The results showed that these gel-gold nanoparticles were degradable with collagenase and promoted significant alkaline phosphatase activity, proliferation, viability, and osteogenic differentiation of stem cells. Moreover, the gel-gold nanoparticles achieved significantly greater new bone formation in vivo, indicating its potential for treating fractured bones.…”
mentioning
confidence: 91%
“…68 Biodegradable gelatin hydrogel incorporating gold nanoparticles (average size 27±3 nm) was also studied. 70 The results showed that these gel-gold nanoparticles were degradable with collagenase and promoted significant alkaline phosphatase activity, proliferation, viability, and osteogenic differentiation of stem cells. Moreover, the gel-gold nanoparticles achieved significantly greater new bone formation in vivo, indicating its potential for treating fractured bones.…”
mentioning
confidence: 91%
“…It is then followed by proliferation, differentiation, and matrix formation [173]. Generally, bone tissue engineering materials requires high mechanical strength of osteoconductive characteristics [174]. However, hydrogel has a low mechanical strength and needs to improve its mechanical properties to mimic bone tissue.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…7 Nanoparçacıkların kemikteki kullanım alanlarının başında rejeneratif tedavide hücre işa-retleyici, kanser ve diğer kemik hastalıklarında ilaç taşıyıcı ve gen taşıyıcı, kemik doku mühendisliğinde ise mineralizasyonu aktive etmek için kaplama ve dolgu maddesi olarak kullanımı gelmektedir. [7][8][9] Nanoparçacıkların günlük yaşamda kullanım-larına ilişkin çalışmaların artışına paralel olarak, bu parçacıkların insan ve çevre sağlığı üzerine etkilerine ilişkin araştırmalar da giderek artmaktadır. Doğal ortamda veya kullanılan ürünlerde bulunan nanoparçacıklar bulundukları ortamdan kolaylıkla ayrılarak havaya, havadan da solunum yoluyla vü-cuda geçmektedirler.…”
unclassified